PENGARUH KEPUASAN PELANGGAN TERHADAP LOYALITAS MEREK PADA PENGGUNA KARTU PRA-BAYAR SIMPATI - Suryani Murad (Jurnal Ilmiah Manajemen Muhammadiyah Aceh, 2011)
Customer Satisfaction is an initial factors to influence the intention of customers to make a repeat buying. Mark loyality is a decision by customers to buy a certain mark in comparison to the others inÂ  the same category of product.The research question is how much the influence of customer satisfaction on mark loyality for Simpati pre-paid card users.Primary data was collected directly through its object which is pre-paid card users in Banda Aceh. while Secondary data was from archival research and literature. The sample of the study consists of 50 Muhammadiyah Aceh University students users of Simpati Pre-paid card.The result of the study exhibits that customer satisfaction significantly influenceÂ  mark loyality for Simpati pre-paid card users. It is shown by somee factors namely expectation, product performance, comparability, confirmation and unsuitable. The most dominat factor is expectation, followed by product performance. Thus, the increase in ecpectation and product performance lead to the increase in mark loyality for Simpati pre-paid card users. Â